Predictors of Emotional Symptoms During Residential Lockdown due to the COVID-19 Pandemic in El Salvador - Orellana, Carlos Iván (2020)
Objective. To explore emotional symptomatology and its predictors in a Salvadorean sample in residential lockdown due to the COVID-19 pandemic. Method. A non-probabilistic sample of 339 participants over 18 years of age, 62% women and 38% men, mostly working people (52.8%), was collected. An online questionnaire recorded behaviors and perceptions during the pandemic, as well as emotional symptoms, using the DASS-21 scale. Results. Around 75% of the sample reported mild emotional symptoms. Compared to men and those employed, women and those engaged in other activities reported more emotional symptoms. Fear of contagion, younger age, and disruption of daily routines were core predictors of emotional symptoms.